Small Molecule Activation by Two‐Coordinate Acyclic Silylenes - Fujimori, Shiori; Inoue, Shigeyoshi (European journal of inorganic chemistry, 2020)
In recent decades, the chemistry of stable silylenes (R2Si:) has evolved significantly. The first major development in this chemistry was the isolation of a silicocene which is stabilized by the Cp* (Cp* = η5‐C5Me5) ligand in 1986 and subsequently the isolation of a first N‐heterocyclic silylene (NHSi:) in 1994. Since the groundbreaking discoveries, a large number of isolable cyclic silylenes and higher coordinated silylenes, i.e. Si(II) compounds with coordination number greater than two, have been prepared and the properties investigated. However, the first isolable two‐coordinate acyclic silylene was finally reported in 2012. The achievements in the synthesis of acyclic silylenes have allowed for the utilization of silylenes in small molecule activation including inert H2 activation, a process previously exclusive to transition metals. This minireview highlights the developments in silylene chemistry, specifically two‐coordinate acyclic silylenes, including experimental and computational studies which investigate the extremely high reactivity of the acyclic silylenes. Silylenes (:SiR2), the heavier analogues of carbenes (:CR2), have recently shown fascinating modes of reactivity, which are conventionally the domain of transition‐metal complexes. This minireview focuses on the developments in silylene chemistry, specifically two‐coordinate acyclic silylenes, including experimental and computational studies attempting to investigate the remarkable high reactivity of the acyclic silylenes.